1942
DOI: 10.1152/ajplegacy.1942.137.1.153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrochloric Acid on the Pyloric Sphincter, the Adjacent Portions of the Digestive Tract and on the Process of Gastric Evacuation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1944
1944
1989
1989

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The difference between their findings and ours is probably related to the longer period of instillation of acid in our tests. Quigley et al (1942) found only a decrease in pressure and an inhibition of motility in the region when acid was injected into the duodenum, but their fixed detectors may not have been located at the site of the increased pressure. Their results suggest that their detectors rested in the terminal antrum, which is inhibited by acid in the duodenum.…”
Section: T T T T T Tmentioning
confidence: 93%
See 1 more Smart Citation
“…The difference between their findings and ours is probably related to the longer period of instillation of acid in our tests. Quigley et al (1942) found only a decrease in pressure and an inhibition of motility in the region when acid was injected into the duodenum, but their fixed detectors may not have been located at the site of the increased pressure. Their results suggest that their detectors rested in the terminal antrum, which is inhibited by acid in the duodenum.…”
Section: T T T T T Tmentioning
confidence: 93%
“…For example, Brody, Werle, Meschan, and Quigley (1940), using air-filled, open-tip catheters on either side of the pylorus in dogs, found no sustained pressure elevation in the zone. The introduction of acid or of fat into the duodenum produced relaxation in the region rather than contraction (Quigley, Read, Radzow, Meschan, and Werle, 1942;Quigley, Werle, Ligon, Read, Radzow, and Meschan, 1941). Atkinson, Edwards, Honour, and Rowlands (1957) detected no increase of pressure as small air-filled balloons and air-filled, open-tipped tubes were withdrawn through the gastroduodenal junctional zone of human beings.…”
mentioning
confidence: 99%
“…Hitherto, the effects of duodenal bolus injections of hydrochloric acid, fat or fatty acids on the intraluminal pyloric pressure have been studied both in humans and dogs. The results were contradictory: some authors found an apparent increase of the basal pyloric pressure (Quigley, Read, Radzow, Meshan & Werle, 1942;Brink et al 1976), whereas other investigators recorded a relaxation of the entire pyloric sphincter region rather than a contraction (Quigley et al 1942). Little is known as to whether the pyloric sphincter might impede gastric evacuation by its phasic contractions or by its degree of relaxation.…”
Section: Pyloric Activitymentioning
confidence: 97%
“…As far as the secretion is concerned, recent studies have supported the importance of a normal vagal supply in the effects of acid (26,28) and hyperosmolar agents (27). Clas sical studies of gastric motility report discordant results, some authors claiming that vagotomy suppresses the effects of acid (19,23) and others indicating that only coeliac ganglionectomy can alter acid inhibition (21). Recently, Cooke and Clarke (5) suggested a non-«-and non-0-adrenergic mechanism in the inhibition by acid in the first 5 cm of duodenum.…”
Section: Introductionmentioning
confidence: 99%